Métodos de manejo para Liriomyza sativae Blanchard, 1938 (Diptera: Agromyzidae - Tamashiro, Luiza Akemi Gonçalves (2021)
Leafminer (Liriomyza spp.) (Diptera: Agromyzidae) are insects distributed throughout the world, have a polyphagous habit, feed on a wide variety of hosts belonging to the Fabaceae, Curcubitaceae and Solanaceae family. They have developmental behavior in the leaf mesophyll, causing the formation of galleries in the leaves. The injuries can result in a reduction in the photosynthetic rate of the plant, drying and loss of leaves and, consequently, a reduction in fruit production. The application of synthetic insecticides is the main control strategy for these pest species. However, the excessive use of these products causes problems such as human and environmental contamination and genotype resistance. Thus, research related to more sustainable management strategies is of great relevance. The objective of this research was to develop alternative control strategies through studies with (1) attractive substances for the capture of adults of L. sativae (2) insecticidal and deterrent effect of essential oils and major compounds on different phases of L. sativae, 3) evaluate the compatibility of entomopathogenic nematodes with essential oils, fixed oils and major compounds in the infectivity of L. sativae larvae. From the results obtained, it was found that: (1) formulations containing banana vinegar (10%), molasses (10%) and citric acid (0.5%) and invert sugar (3%), molasses (5%), hydrolyzed protein (0.5%) and citric acid (0.5%) captured the largest number of adults of L. sativae during the period of 12 and 14 days, respectively, compared to the other formulations, (2) citronella essential oil showed the highest toxicity in L. sativae larvae and neem oil the highest deterrence in adults compared to other oils, (3) essential oils, fixed oils and major compounds caused mortality, reduced number of lateral body strokes and infectivity in L. sativae larvae, with emphasis on eucalyptus, ginger and rosemary oils. The evaluated strategies can be used to help reduce the population of L. sativae in integrated management programs.